ANALISIS HUBUNGAN KUALITAS AIR MINUM DAN KEJADIAN DIARE DI WAWONDULA SEBAGAI WILAYAH PEMBERDAYAAN PT. VALE SOROWAKO - Andi Zulkifli; Kristiawan Basuki Rahmat; Andi Ruhban (Politeknik Kesehatan Makassar, 2017)
Diarrhea is still a major health problem, especially in developing countries, including Indonesia. The purpose of this study was to analyze the relationship between drinking water quality and diarrhea occurrence in the empowerment area of PT.Vale Indonesia. This study used cross sectional design which is one of the analytic epidemiological research designs, and included in observational research type with diarrhea respondents from January to July 2016. The results showed the relationship between the distance of pollutant sources with bacteriological quality, the construction of clean water facilities with bacteriological quality and the quality of drinking water with the occurrence of diarrhea. Significantly related variables were bacteriological quality (0.02), treatment action (0,000) and hygiene behavior (0.000). The most influential variable on the occurrence of diarrhea is the processing action. Based on the result of research, it is concluded that, the distance of dug well with pollutant source, dug well construction and processing action affect drinking water quality and diarrhea occurrence. Keywords: Diarrhea, Bacteriological Quality, Hygiene Behavior